Development of calculation schemes for the combined extrusion to predict the shape formation of axisymmetric parts with a flange - Vlasenko, Kateryna; Hrudkina, Natalia; Reutova, Irina; Chumak, Olena (Eastern-European Journal of Enterprise Technologies, 2018)
We have developed calculation schemes for the process of combined radial-reverse extrusion of parts with a flange. Based on the energy method, we have derived formulae for calculating the reduced pressure of deformation and a phased increase in the dimensions of a semi-finished product. Relevance of the research is based on ensuring the simplification of estimation of the application of a given deformation process to obtain parts with a required configuration. In addition, we have proved the efficiency of determining the limit of using the derived calculation scheme for ratios 2h1R2/(R22–R12)<1. We analyzed a product range manufactured at the enterprises of machine-building and instrument-making, which includes a significant number of hollow parts with flanges and branches of various shapes. It was substantiated that the use of combined extrusion schemes in the manufacture of parts of the type «a cup with a flange», when compared to employing simple deformation techniques, improves technological possibilities of the process. That is achieved through the reduction in energy costs, as well as in the number of technological transitions, and through making the shape of the parts obtained more complex. We confirmed the lack of proper studies into technologies for the implementation of combined extrusion schemes and the absence of appropriate technological recommendations. We determined the power mode of extrusion that corresponds to reality and estimated a possibility to control the outflow of metal at deformation. A study was conducted into the process of cold combined extrusion of hollow parts with a flange; the calculation schemes of the process were proposed. We modeled the process of combined extrusion based on the experimental-analytical method and established patterns in the shape formation of parts with a flange due to the geometrical and technological parameters. Data were acquired on the phased form change in a semi-finished product in the process of deformation. It was confirmed that the proposed models simplify the development of technological recommendations to determine the power mode of extrusion and to control the outflow of metal during deformation process.